THE EFFECT OF GIVING LYSINE AND METHIONINE AMINO ACIDS THROUGH DRINKING WATER TO THE EGGS PRODUCTION OF PUREBRED CHICKEN - V. A. M ., Asmara; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This research was conducted to determine the effect of giving lysine and methionine amino acids through drinking water on egg production of purebreed chicken. This research was conducted in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province for 4 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications, each replication consisting of 10 chickens. The treatments are: P0 (chicken given drinking water without lysine and methionine), P1 (chicken given drinking water with 0.1% lysine and methionine), P2 (chicken given drinking water with 0.15% lysine and methionine), and P3 (chicken given drinking water with 0.2% lysine and methionine). The variables observed were feed consumption, water consumption, Hen Day Production (HDP), total egg weight, average egg weight, and feed conversion. The results showed that feed consumption, water consumption, and Hen Day Production (HDP) did not show statistically significant differences (P>0.05) in the four treatments. The total egg weight at P0 was 458.12 grams, while P1, P2, and P3 were 22.4%, 11.8%, and 5.21%, respectively, which were significantly higher (P<0.05). The average of egg weight of P0 is 55.53 grams, while P1, P2, and P3 are 9.13%, 5.47%, and 2.08%, respectively, significantly higher (P<0.05). The feed conversion of P0 is 2.13, while P1, P2, and P3 were 15.1%, 6.5%, and 2.4%, respectively, significantly higher (P<0.05). Based on the results of this research, it can be concluded that the giving of lysine and methionine amino acids through drinking water not effect feed consumption, water consumption, and Hen Day Production (HDP), but increasing total egg weight, average egg weight and reducing total egg weight ad feed convertion ration conversion rate.